2016
DOI: 10.1038/pr.2016.97
|View full text |Cite
|
Sign up to set email alerts
|

Safety and pharmacokinetics of multiple dose myo-inositol in preterm infants

Abstract: BACKGROUND Preterm infants with RDS given inositol had reduced BPD, death and severe ROP. We assessed the safety and pharmacokinetics(PK) of daily inositol to select a dose providing serum levels previously associated with benefit, and to learn if accumulation occurred when administered throughout the normal period of retinal vascularization. METHODS Infants ≤29wks GA (n=122, 14 centers) were randomized and treated with placebo or inositol at 10, 40 or 80mg/kg/day. Intravenous administration converted to ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…Myo has been used in preterm infants (<29 weeks of gestational age) with respiratory distress syndrome in order to assess safety and pharmacokinetics of different daily inositol doses (10, 40, or 80 mg/kg/d). In this setting, treatment with Myo 80 mg/Kg/die for more than 10 weeks did not result in increased incidence of any adverse event as compared with control babies …”
Section: Inositol Safetymentioning
confidence: 74%
“…Myo has been used in preterm infants (<29 weeks of gestational age) with respiratory distress syndrome in order to assess safety and pharmacokinetics of different daily inositol doses (10, 40, or 80 mg/kg/d). In this setting, treatment with Myo 80 mg/Kg/die for more than 10 weeks did not result in increased incidence of any adverse event as compared with control babies …”
Section: Inositol Safetymentioning
confidence: 74%
“…The dose of myo-inositol to produce serum concentrations was similar to those in the previous studies. 5,6,15 However, the combination of longer treatment and the inclusion of infants with younger gestational ages may have resulted in the unexpected increase in mortality through as yet unknown mechanisms. In vitro data have shown that infection of macrophages by some intracellular bacteria is enhanced by their ability to use myo-inositol as an energy source.…”
Section: Discussionmentioning
confidence: 99%
“…After conducting pharmacokinetic and safety studies of myo-inositol in extremely preterm infants, a dose of 40 mg/kg every 12 hours was selected to achieve serum concentrations similar to those previously reported. 14,15 A therapeutic duration of up to 10 weeks was chosen to sustain serum myo-inositol levels similar to those found in utero throughout the period of normal retinal vascular development and because of the reported benefits in the treatment of ROP and survival. 12 The placebo was a solution of 5% glucose for intravenous infusion from pharmacy stock.…”
Section: Interventionmentioning
confidence: 99%
“…After contemporary evaluations of the pharmacokinetics of inositol in preterm infants, a recent RCT was suspended at 36% enrollment because of a manufacturing problem with the drug. 21,22 Of note, inositol is a nutritional supplement that can be used without oversight by the US Food and Drug Administration, although a parenteral form of the sugar is not available. On review by the DSMC, death was increased from 11% with the placebo to 18% with inositol supplementation (P = .007), severe retinopathy was qualitatively but not statistically increased, and there was no effect on BPD.…”
Section: Inositol Supplementation Of Preterm Infantsmentioning
confidence: 99%